2009
DOI: 10.1149/1.3206618
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Incorporation in Al2O3 Thin Films Prepared by Pulsed Ultrasonic Sprayed Pyrolysis

Abstract: The electrical characteristics and the chemical composition profiles determined by XPS and SIMS for aluminum oxide thin films deposited by pulsed ultrasonic spray pyrolysis are reported. The films were deposited on c-Si at 550 ºC using a chemical solution of aluminum acetylacetonate as source of aluminum and N,NDimethylformamide as solvent, in addition a H 2 O-NH 4 OH mist was supplied simultaneously during deposition to improve the overall properties of these films. The results show that there is nitrogen inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The reduction of the breakdown field observed for films deposited at higher temperatures (600 and 650 • C) is not clearly understood and further experimentation is required to be able to address this point properly. In general these films show better insulating characteristics than La 2 O 3 and Al 2 O 3 , deposited by reactive radiofrequency sputtering and pulsed ultrasonic spray pyrolysis 15,31 and similar to those reported for lanthanum-aluminum oxide synthetized by atomic layer deposition. 2,29 It should be mention that the films in the current paper are much thicker than typical ALD films, since thicker films could be expected to show lower current leakage and direct comparison between the results for these two techniques should be taken with the caution.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The reduction of the breakdown field observed for films deposited at higher temperatures (600 and 650 • C) is not clearly understood and further experimentation is required to be able to address this point properly. In general these films show better insulating characteristics than La 2 O 3 and Al 2 O 3 , deposited by reactive radiofrequency sputtering and pulsed ultrasonic spray pyrolysis 15,31 and similar to those reported for lanthanum-aluminum oxide synthetized by atomic layer deposition. 2,29 It should be mention that the films in the current paper are much thicker than typical ALD films, since thicker films could be expected to show lower current leakage and direct comparison between the results for these two techniques should be taken with the caution.…”
Section: Resultssupporting
confidence: 84%
“…This type of behavior has been observed previously in Al 2 O 3 and La 2 O 3 thin films deposited by pulsed spray pyrolysis and cyclic chemical vapor deposition, respectively. 15,16 The possibility that silicon detected on the film surface could be related to pinholes or porosity reaching down to the substrate has been ruled out since in this case a constant distribution of silicon across the film thickness would be expected. It is also observed that the content of lanthanum through the films is not uniform, after a spike at the film surface, the lanthanum content goes to a low value and recovers to a slightly higher value.…”
Section: Resultsmentioning
confidence: 99%
“…The mist is transported through a glass tube to the substrate surface which is being heated to achieve the pyrolysis reaction. Unlike many other films deposition techniques, spray pyrolysis represents a very simple and relatively cost-effective processing method because doesn't require high-cost vacuum techniques and still yields high electronic quality films, as reported previously for thin aluminum oxides films (8).…”
Section: Introductionmentioning
confidence: 84%
“…The mist is transported through a glass tube to the substrate surface which is being heated to achieve the pyrolysis reaction. Unlike many other films deposition techniques, spray pyrolysis represents a very simple and relatively cost effective processing method because doesn't require high cost vacuum techniques and still yields high electronic quality films, as reported previously for thin aluminum oxides films [8]. In this case, lanthanum nitrate and aluminium acethylacetonate were dissolved in N,N dimethylfolmamide to obtain the spray solution.…”
mentioning
confidence: 99%